Methodology for an effective retrofitting strategy of existing masonry buildings: a case study near L'Aquila. (8th January 2021) - Sandoli, Antonio; Calderoni, Bruno
The whole Mediterranean area historical heritage is mostly constituted by 'ancient' unreinforced masonry constructions which are particularly vulnerable to earthquakes. Due to the particular attitude to out-of-plane collapse mechanisms, 'ancient' constructions largely contribute to increase the seismic risk. In this paper, a methodology for retrofitting unreinforced masonry buildings, aimed to gradually transforms the 'ancient' masonry building into a 'modern' code-conforming building, is proposed. This approach has been applied to an existing masonry building located near L'Aquila (Italy) and damaged during the 2009 earthquake. The results demonstrate the usefulness of a methodological approach to implement retrofitting actions. Thus, appears more easily to calibrate the interventions as a function of the structural weakness and to quantify the role of each intervention in terms of capacity-to-demand ratio. Moreover, a gradual control of the seismic performance enhancement with respect to the original capacity can be achieved, avoiding high economic costs related to unnecessary interventions.